Structural and physicochemical properties of silver-rich Ag–Al alloys. (March 2020) - Terlicka, S.; Dębski, A.; Gierlotka, W.; Wierzbicka-Miernik, A.; Budziak, A.; Sypien, A.; Zabrocki, M.; Gąsior, W.
Abstract: The X-ray diffraction, Scanning Electron Microscopy, Differential Scanning Calorimetry, dilatometric and electrical conductivity measurements were used to study the structural and physicochemical properties of selected silver-rich alloys from Ag–Al system. All the studied alloys, containing from 10 to 37 at. % of Al (Ag90 Al10, Ag85 Al15, Ag77 Al23, Ag75 Al25, Ag72 Al28, Ag70 Al30, Ag63 Al37 ), were prepared from high purity metals by melting in a glove-box filled with a high purity argon atmosphere. The obtained X-ray diffraction patterns and microstructure observation of alloys containing up to 15 at. % of Al suggested that in this range only solid solution of silver exists. The thermal analysis showed heat effects related to phase transitions in Ag–Al system. In addition, the thermal expansion studies revealed an anomalous behavior in expansion for some composition of alloys associated with the phase transition. The electrical conductivity values rapidly changed, which may be associated with the formation of different phase areas in the Ag–Al system. Based on the results obtained in this work and critically reviewed literature data a thermodynamic re-optimization of the binary Ag–Al system using CALPHAD method was proposed. A good agreement between calculation and experiment was found. Highlights: The X-Ray Diffraction analysis of investigated Ag–Al alloys. Microstructure observation of selected Ag–Al alloys. DSC and dilatometric measurements of Ag-rich alloys from Ag–Al system. Electrical conductivity of seven alloys from Ag–Al system. Thermodynamic re-optimization of the binary Ag–Al system based on newest experimental data.